Higher-Order Thinking Skill (HOTs) Questions in English National Examination in Indonesia - Putra, Tomy Kartika; Fikky Abdullah, Debiga (Universitas Negeri Semarang, 2019)
The using of HOTS questions to stimulate the learners’ thinking skills is essential to meet the challenge of 21st century. However, we know little about to what extent and what particular aspects of HOTS implemented in Indonesia English National Examination. Therefore, in order to fulfil the gap, the present study attempts to identify the use of HOTS-based questions and what particular skills appearing under HOTS category in English National Examination. We examine one package of each English National Examination from 2013 until 2018. We analyse 210 multiple-choice items in which each examination contain 35 items of reading comprehension. The items are analyzed quantitatively through content analysis based on the aspects of HOTS in Revised Bloom’s Taxonomy. The researchers find that there is insufficient amount of HOTS questions in English National Examination. 157 items classified into the LOTS and only 53 (25.23%) items are classified into HOTS. The second finding is that the level of HOTS included in English National Examination 2013-2018 is only the level of Analyze. The Differentiating and Organizing are the subskills of the aspect of Analyze that are mostly included in all examinations. There is strong evidence for encouraging the test developers to provide adequate portions of HOTS-based items in English National Examination. Keywords: Higher-order thinking skill, Lower-order thinking skill, assessment, English national examination